2018
DOI: 10.1007/s11356-018-2085-0
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study investigating the effects of dilution by precipitation on dissolved inorganic carbon and stable isotope evolution in surface waters

Abstract: Surface waters are a major pathway of carbon cycling between the atmosphere and the earth's surface. Yet studies describing water column processes that affect carbon cycling do not consider the effects of dilution by precipitation. In this study, we conducted a laboratory experiment in which we prepared undiluted (100%) and snowmelt diluted 25, 50, and 75% by volume of samples of NaHCO solution and lake and river water and then exposed them to the laboratory atmosphere for up to 1000 h. We aim to determine how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The concentration of DIC decreased with increasing river discharge ( r = −0.66, p < 0.01, Figure 5c) as the increasing runoff after precipitation diluted the DIC pool (Abongwa & Atekwana, 2018; Cai et al, 2015; Lee et al, 2017; Reiman & Xu, 2019; Zhong et al, 2017). The imported DIC in high flow was characterized by low concentration and lower δ 13 C, likely from organic‐derived CO 2 (Cerling et al, 1991; Leith et al, 2014; Reiman & Xu, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of DIC decreased with increasing river discharge ( r = −0.66, p < 0.01, Figure 5c) as the increasing runoff after precipitation diluted the DIC pool (Abongwa & Atekwana, 2018; Cai et al, 2015; Lee et al, 2017; Reiman & Xu, 2019; Zhong et al, 2017). The imported DIC in high flow was characterized by low concentration and lower δ 13 C, likely from organic‐derived CO 2 (Cerling et al, 1991; Leith et al, 2014; Reiman & Xu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The surface water evaporation of rivers and lower runoff water input in drier periods could increase the contribution of deep groundwater DIC (Atkins et al, 2017;Barth et al, 2003). Maximum values of [DIC] and δ 13 C-DIC were observed in the extremely dry period (Figures 2c and 4b The concentration of DIC decreased with increasing river discharge (r = À0.66, p < 0.01, Figure 5c) as the increasing runoff after precipitation diluted the DIC pool (Abongwa & Atekwana, 2018;Cai et al, 2015;Lee et al, 2017;Reiman & Xu, 2019;Zhong et al, 2017).…”
Section: Riverine Dic and Co 2 * Magnitudes Sources And Dynamicsmentioning
confidence: 95%
See 1 more Smart Citation
“…This result showed that dilution not only plays an important role in the precipitation effect, but it also affects river water. However, the dilution effect was also significant when precipitation was the major recharge source for river water (Abongwa and Atekwana, 2018;.…”
Section: Meteorological Factorsmentioning
confidence: 99%
“…It was found that the contribution of glacier and snow meltwater to runoff in spring was as high as 82 %. Boucher and Carey (2010) systematically studied runoff segmentation in permafrost basins. Maurya et al (2011) found that the average contribution of meltwater to runoff was 32 % in typical glacial basins on the southern slope of the Himalayas.…”
Section: Introductionmentioning
confidence: 99%